Different mechanisms underlying changes in excitability of peripheral nerve sensory and motor axons in multiple sclerosis. Issue 1 (21st November 2012) - Ng, Karl; Howells, James; Pollard, John D.; Burke, David
Abstract Introduction: Subtle involvement of peripheral nerves may occur in multiple sclerosis. Motor excitability studies have suggested upregulation of slow K+ currents, probably secondary to altered motoneuron properties resulting from the central lesion. This study concentrates on sensory axons. Methods: Excitability of median nerve axons at the wrist was studied in 26 patients. Results: Sensory recordings were possible in 22 patients, and reduced superexcitability was the sole abnormality. There was no evidence for changes in membrane potential or demyelination. The decrease was significant in patients taking immunomodulatory therapy. These findings could be reproduced in a computer model by changing the gating of fast K+ channels. Motor axon findings were consistent with previously reported increased slow K+ current. Conclusions: The sensory findings differ from motor findings. They can be explained by a humoral factor, possibly cytokines, which can penetrate the paranode and have been documented to alter the gating of K+ channels. Muscle Nerve, 2013